Biological chitin-MOF composites with hierarchical pore systems for air-filtration applications - Wisser, Dorothea; Wisser, Florian M.; Raschke, Silvia; Klein, Nicole; Leistner, Matthias; Grothe, Julia; Brunner, Eike; Kaskel, Stefan (Angewandte Chemie International Edition, 2015)
Metal-organic frameworks (MOFs) are promising materials for gas-separation and air-filtration applications. However, for these applications, MOF crystallites need to be incorporated in robust and manageable support materials. We used chitin-based networks from a marine sponge as a non-toxic, biodegradable, and low-weight support material for MOF deposition. The structural properties of the material favor predominant nucleation of the MOF crystallites at the inside of the hollow fibers. This composite has a hierarchical pore system with surface areas up to 800 m2-g-1 and pore volumes of 3.6 cm3-g-1, allowing good transport kinetics and a very high loading of the active material. Ammonia break-through experiments highlight the accessibility of the MOF crystallites and the adsorption potential of the composite indicating their high potential for filtration applications for toxic industrial gases. Sponge bag: A composite material is formed from a metal-organic framework (MOF) and a chitin biopolymeric network extracted from a marine sponge. The inner surface functionalities of the biomatrix cause the MOF HKUST-1 (Cu3BTC2) to crystalize inside the hollow chitin fibers, resulting in a hierarchical pore system with a surface area of up to 800 m2-g-1. The composite shows a high affinity for toxic industrial gases such as NH3.
CRIS-Team Scopus Importer:2023-03-20
Keywords: chitin; Cu; marine sponge; metal-organic frameworks; NH